2008
DOI: 10.1159/000162270
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Health-Related Quality-of-Life Outcomes after Permanent Prostate Brachytherapy

Abstract: Background: We evaluated the long-term health-related quality of life (HRQoL) after modern prostate brachytherapy (PB). Patients and Methods: The European Organization for Research and Treatment of Cancer (EORTC) prostate cancer quality-of-life questionnaire, QLQ-PR25, and the modified International Continence Society (ICS) male questionnaire were sent to 296 men treated with PB at the University Medical Center Mannheim. To evaluate the influence of age, we subclassified two groups: group 1 <65 years, group 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Nevertheless, bowel toxicity at follow‐up was low: only 2.9% of patients reported moderate bowel toxicity and none reported severe toxicity. These findings are consistent with those of previous studies [21,23,26–28,32].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, bowel toxicity at follow‐up was low: only 2.9% of patients reported moderate bowel toxicity and none reported severe toxicity. These findings are consistent with those of previous studies [21,23,26–28,32].…”
Section: Discussionsupporting
confidence: 94%
“…In view of that equivalence, post‐treatment QoL secondary to urinary symptoms, maintenance of sexual function and normal bowel function are becoming increasingly important to both physicians and patients when deciding which modality is probably the most suitable. Several studies have reported toxicity outcomes within the first few years after treatment [11,15–27] but there have been fewer longer‐term studies of those considerations [3,28–33]. In the present study, we assessed various aspects of QoL and sexual function up to 10 years after prostate BXT, with a good response rate to the request for follow‐up information (77%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Schafer, et al28 showed that only 10.4% and 1% of men reported moderate and severe urinary symptoms, respectively, whereas Koontz, et al29 reported that acute GU toxicity and GI toxicity occurred in approximately 80% and 24% of patients, respectively, and that late GU toxicity and GI toxicity occurred in 21% and 38% of patients, respectively. In our series, late GU toxicity was observed in nearly 96% of all patients, but 65% of them were classified as RTOG toxicity grade <3, which was controlled by medication.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials comparing the different therapeutic concepts do not exist, but there are large cohort studies with PSA-free survival rates comparable to a treatment with radical prostatectomy or external-beam radiotherapy [27,30,36] and low toxicity rates [26]. The prescribed dose for LDR brachytherapy with iodine-125 ( 125 I) seeds is 145 Gy.…”
Section: Brachytherapymentioning
confidence: 99%